2016
DOI: 10.1021/acs.nanolett.6b02971
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Solar Cell Photovoltage via Nanophotonic Engineering

Abstract: Approaching the theoretically limiting open circuit voltage (V) of solar cells is crucial to optimize their photovoltaic performance. Here, we demonstrate experimentally that nanostructured layers can achieve a fundamentally larger Fermi level splitting, and thus a larger V, than planar layers. By etching tapered nanowires from planar indium phosphide (InP), we directly compare planar and nanophotonic geometries with the exact same material quality. We show that the external radiative efficiency of the nanostr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 41 publications
2
53
0
Order By: Relevance
“…A similar strategy involving branched TiO 2 NRs (so-called nano-dendrites or ND) has been demonstrated to achieve modest improvements in the performance of HPSCs through enhancement of light trapping as shown in Figure 14 [152]. Cui et al [153] demonstrated that a nanostructured active layer could achieve a fundamentally larger V oc than planar layers through both increased quasi-Fermi level splitting and enhanced radiative outcoupling efficiencies. …”
Section: Exploitation Of Nanophotonic Effects In 1d-etlsmentioning
confidence: 99%
“…A similar strategy involving branched TiO 2 NRs (so-called nano-dendrites or ND) has been demonstrated to achieve modest improvements in the performance of HPSCs through enhancement of light trapping as shown in Figure 14 [152]. Cui et al [153] demonstrated that a nanostructured active layer could achieve a fundamentally larger V oc than planar layers through both increased quasi-Fermi level splitting and enhanced radiative outcoupling efficiencies. …”
Section: Exploitation Of Nanophotonic Effects In 1d-etlsmentioning
confidence: 99%
“…With their unique structural, optical, and electrical properties, III-V semiconductor nanowires (NWs) have shown great potential for novel nanoscale device applications, such as light-emitting diodes (LEDs), 1 lasers, 2-4 photodetectors, [5][6][7] and solar cells. [8][9][10] In particular, semiconductor NWs are considered to be highly promising for next-generation photovoltaic devices due to (1) their intrinsic antireflection effect for enhancing light absorption, (2) their small footprint efficiently relaxing the lattice-mismatched strain and thus enabling the construction of multijunction cells with optimal band gap combinations as well as the growth on different substrate materials such as silicon and thus potential integration with the existing silicon-based industrial infrastructures, 11,12 and (3) significant cost reduction due to much less material usage.…”
Section: Introductionmentioning
confidence: 99%
“…Approaching the theoretical V oc limit of PV cells is therefore crucial to optimizing their performance. It has also been shown that nanostructured devices can achieve a larger Fermi level splitting based on enhanced photon escape probabilities as well as the smaller volume elements . Therefore, a V oc enhancement in devices based on nano‐scale layers may be expected compared to devices based on more standard bulk layers.…”
Section: Introductionmentioning
confidence: 99%